The Phenomenon of Egocentrism in the Poetic Discourse (on the Material of Discourse Analysis of Stepan Rudanskyy’s Humorous Poetic Pieces) (Linguostylistic Studies, 2015)
The article dwells upon the specificities of Stepan Rudanskyy’s humorous poetic pieces discourse. They represent Ukrainians’ everyday speech, whose specificity is the egocentrism of borrowings. It verbalizes simultaneously two theories of accentualisation, an expressive attention drawing to the text, – the theory of tension and the theory of digression. The above-mentioned egocentrism is motivated by the “speech biography” of the writer. Multilingualism and polyglossia were peculiar to S. Rudanskyy. He knew several foreign languages – Ukrainian, Russian, Polish, German. It encouraged him to develop and enrich his native Ukrainian language, to introduce a number of borrowings – calques, half-calques, macaronic speech, exoticisms. In the humorous poetic pieces discourse they perform a number of pragmatic functions: intensification of the expression, emotionality, raciness, a brighter presentation of the Ukrainians the 19th century, real way of speaking. While using the borrowings, S. Rudanskyy made mistakes, both intentional and spontaneous, which are described in the article. The research promotes a comprehensive portrait of S. Rudanskyy’s lingual personality, which is still to be developed. Key words: egocentrism of borrowings, real speech, theory of accentualisation, theory of tension, theory of digression, polyglossia of discourse, «speech biography». References